(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
The article analyses Zuzanna Ginczanka’s poem Nature morte: Tomato, wherein the poet transforms a visual artwork into a lyrical expression. The introduction establishes a contemporary definition of ekphrasis and revisits its interpretation by ancient rhetoricians, emphasizing the concept of enargeia as an essential quality of ekphrasis. This theoretical framework culminates in a discussion of the intersections between painting and poetry. The poem analysis focuses on the visualization techniques employed by Ginczanka. Two levels of enargeia are identified within her text: one that is readily apparent and another that is more concealed, necessitating linguistic analysis for its extraction. This duality enriches the understanding of how visual elements can be articulated through poetic language, revealing deeper layers of meaning and enhancing the reader’s engagement with both the visual and literary art forms.